Partisipasi Masyarakat Dalam Implementasi Kebijakan Layanan Ruang Menyusui Di Kota Banda Aceh - Mira Gusweni (Puslatbang KHAN, 2020)
This qualitative study aims to describe and analyze community participation in the implementation of breastfeeding room service policy in Banda Aceh city using the CLEAR Model. The result shows that: (1) The breastfeeding rooms are not provided in all government offices or public places in Banda Aceh, and most of the rooms do not meet the Ministry of Health's standard; (2) The community gives a positive response and considers that this policy is beneficial. They hope that the implementation of this policy is continued and available in other public places. Public participation bases on the CLEAR model is the availability of sources of information and education such as posters and the direction signs to the breastfeeding room, and the mothers a can access the room comfortably. Furthermore, this research also found that the factors contribute to low access to the room are the habit of the mothers breastfeeding in the public space, and the poor quality of the rooms. Also, there is no specific socialization to the public about the implementation of the policy. Thus, increasing of public socialization regarding this regulation should employ communication, information and education (CIE) methods and fulfilment of breastfeeding room standards in Banda Aceh.